RESPON TANAMAN KACANG TANAH (Arachis hypogaea L.) VARIETAS TALAM-1 TERHADAP BERBAGAI JARAK TANAM DAN PEMBERIAN FUNGI MIKORIZA ARBUSKULAR - Khairuni, Suci; Syafrinal, Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Demands on peanuts in Riau Province increasing every year while the production decreases, resulting in the unfulfilled demands on peanuts. Efforts that need to be done to overcome this obstacles are finding the suitable planting space to plant talam-1 varieties and giving arbuscular mycorrizhal fungi (AMF) to help absorb the plant nutrients. The research aims are to find out the effect of planting space and arbuscular mycorrhizal fungi distribution to growth and production of peanuts (Arachis hypogaea L.) talam-1 varieties and to find the best treatment. This research is factorial experiment which is arranged based on RAL with two factors. Factor I is planting space with two levels J1:40cm x 20cm and J2: 40cm x 40cm. Factor II is the dosage of arbuscular mycorrhizal fungi with four levels H0:withoutAMF, H1: AMF 5g per plant, H2: AMF 10g per plant and H3: AMF15g per plant.The result shows that planting space management and arbuscular mycorrhizal fungi distribution are yet able to increasethe peanut’s growth and production on all parameters, exceptthe hight parameter of peanuts (Arachis hypogaea L). Keyword(s): peanut, plant space, arbuscular mycorrhizal fungi,production.